Large Carnivores of the Chernobyl Nuclear Power Plant Exclusion Zone - Shkvyrya, M.; Vishnevskiy, D. (Вестник зоологии, 2012)
During nine years observations on large carnivores of Exclusion Zone have been carried out. Species composition and the number of large predators in the Exclusion Zone correspond to the regional conditions. The presence of bears and permanent stay of the lynx in the Exclusion Zone was confirmed. Six wolf packs were counted. The use of an anthropogenically transformed areas, the shift of the daily regime of activity and characteristics of the diet are the most specific features of this animal group.